Intact and Damaged Wheat Starch and Amylase Functionality During Multilayered Fermented Pastry Making. Issue 10 (12th September 2018) - Ooms, Nand; Vandromme, Evert; Brijs, Kristof; Delcour, Jan A.
Abstract : Abstract: The roles of native and damaged starch (DS) during fermented pastry making were examined by increasing the level of DS in wheat flour by ball‐milling and/or by including amylase in the recipe. Increased DS levels increase laminated dough strength presumably by making less water available for the gluten. This effect was partly overcome by amylase use. During baking, a reduced resistance of the dough to gas cell expansion, as a result of enzymatic starch hydrolysis, seems responsible for increased pastry lift and improved crumb structure. Gelatinization of intact starch limits dough lift and expansion. Even at high amylase dosages structural collapse was limited, which suggests a significant role for gluten in pastry product structure formation. Differential scanning calorimetry and low‐resolution 1 H nuclear magnetic resonance experiments indicated that increased levels of starch damage and amylase use impact the amylose network in the product and respectively increase and decrease the extent to which amylopectin retrogrades during storage. Practical Application: This research article evaluates the role of intact and damaged wheat starch during the production of fermented pastry products. An expanded knowledge on starch functionality during the different pastry production steps allows for a targeted selection of additives to improve product quality and production efficiency. The results obtained in this study can contribute to the realization of industrially feasible solutions for the production of quality pastry products.